Optimized design of a semimetal gasket operating in flange-bolted joints - Jaszak Przemysław (De Gruyter, 2020)
The paper presents a new design of semimetal gasket, which has been subjected to the optimization process. The main objective function was to achieve the maximum elastic recovery of the gasket at imposed functional and strength limitations. The objective function was described indirectly in the form of the required minimum angle of the gasket’s unload curve inclination, which was a measure of the average value of the elastic modulus at unloading. Strength limitations resulted from not exceeding the ultimate stress of the materials, while functional limitations imposed the achievement of proper contact pressure that ensures a given level of tightness class. The characteristic dimensions describing the cross-section of the gasket’s core were described by five descriptive parameters. As a result of the interrelationship of these parameters, 210 construction models were created that were subjected to compression simulations. This problem was solved using the Finite Element Method. The variant of the gasket fulfilling the imposed limitations and the required minimum objective function was tested experimentally.